“There is much more to communication than just language”: Intercultural training for English majors - Wach, Aleksandra; Cholewa, Wiktoria (Neofilolog, 2025)
The article presents the results of a mixed-methods study conducted during an elective proseminar in which the participants (N = 34), English majors in the undergraduate program, received intercultural training. The aims of the study were to find out which dimensions of intercultural competence were developed as a result of the training and to investigate the participants’ opinions about the usefulness of the course for the development of their intercultural competence. The research data were collected through the Intercultural Sensitivity Scale (Chen, Starosta, 2000) administered before and after the training, and the participants’ written evaluations of the course. The quantitative analysis revealed significant increase in three out of five components of the scale: interaction engagement, confidence, and attentiveness. These results were complemented and elaborated upon by the qualitative findings, which uncovered the participants’ perceptions about the benefits of the training in enhancing their knowledge about interculturality and communication, various skills, and positive attitudes. They also pinpointed the teaching procedures that helped them develop.